Stage‐dependent regulation of oligodendrocyte development and enhancement of myelin repair by dominant negative Master‐mind 1 protein. Issue 9 (30th April 2019) - Ge, Xinqi; Xiao, Guanxiu; Huang, Hao; Du, Junqing; Tao, Yanmei; Yang, Aifen; Wu, Huihui; Zhang, Zunyi; Qiu, Mengsheng
Abstract: Notch signaling has been implicated in the inhibition of oligodendrocyte differentiation and myelin gene expression during early development. However, inactivation of a particular Notch or Hes gene only produces a mild phenotype in oligodendrocyte development possibly due to the functional redundancies among closely related family members. To uncover the full role of Notch signaling in myelin development and regeneration, we generated the Sox10 rtTA/+ ; TetO‐dnMAML1 double transgenic mice in which expression of dominant negative Master‐mind 1 (dnMAML1) gene can be selectively induced in oligodendrocyte precursor cells (OPCs) for complete blockade of Notch signaling. It is found that dnMAML1 expression leads to robust precocious OL differentiation and premature axonal myelination in the spinal cord, possibly by upregulating Nkx2.2 and downregulating Pdgfra expression. Unexpectedly, at late embryonic stages, dnMAML1 expression dramatically increased the number of OPCs, indicating a stage‐dependent effect of Notch signaling on OPC proliferation. In addition, dnMAML1 also significantly enhances axonal remyelination following chemical‐induced demyelination, providing a promising therapeutic target for lesion repair in demyelinating disease. Abstract : Inhibition of Notch signaling robustly promotes oligodendrocyte precursor cell (OPC) differentiation possibly by activating the Nkx2.2 pathway after E14.5. Inhibition of Notch signaling causes increased OPC proliferation and cyclin D1 expression after E16.5, but downregulation of PDGFRa and p27kip1 expression, suggesting that dnMAML promotes OPC proliferation independent of PDGFRa signaling. Inhibition of Notch signaling accelerates developmental myelination and enhances myelin regeneration in adult CNS.